Mastering Communication - Nicky Stanton (New York Palgrave Macmillan, 2009)
This book will help students improve their speaking, listening, reading and writing skills. It will give an understanding of the importance of good communication skills for their personal development and career.
Keywords: Communication; Textbooks; Personal and Professional Development for Business (BIN 1076-N)